TIGIT+Tfh show poor B-helper function and negatively correlate with SARS-CoV-2 antibody titre - Edner, Natalie M.; Houghton, Luke P.; Ntavli, Elisavet; Rees-Spear, Chloe; Petersone, Lina; Wang, Chunjing; Fabri, Astrid; Elfaki, Yassin; Rueda Gonzalez, Andrea; Brown, Rachel; Kisand, Kai; Peterson, Pärt; et al. (Frontiers in Immunology, 2024)
Circulating follicular helper T cells (cTfh) can show phenotypic alterations in disease settings, including in the context of tissue-damaging autoimmune or anti-viral responses. Using severe COVID-19 as a paradigm of immune dysregulation, we have explored how cTfh phenotype relates to the titre and quality of antibody responses. Severe disease was associated with higher titres of neutralizing S1 IgG and evidence of increased T cell activation. ICOS, CD38 and HLA-DR expressing cTfh correlated with serum S1 IgG titres and neutralizing strength, and interestingly expression of TIGIT by cTfh showed a negative correlation. TIGIT+cTfh expressed increased IFNγ and decreased IL-17 compared to their TIGIT-cTfh counterparts, and showed reduced capacity to help B cells in vitro. Additionally, TIGIT+cTfh expressed lower levels of CD40L than TIGIT-cTfh, providing a potential explanation for their poor B-helper function. These data identify phenotypic changes in polyclonal cTfh that correlate with specific antibody responses and reveal TIGIT as a marker of cTfh with altered function.